Implementasi Program Kemitraan Masyarakat Melalui Sosialisasi Standar Laporan Keuangan, Pengendalian Kas dan Akses Pendanaan di Kumala Bali Aksesoris - Ni Luh Putu Mita Miati; Putu Gede Wisnu Permana Kawisana; I Gusti Ayu Athina Wulandari (Jurnal Pengabdian UNDIKMA, 2022)
This service aims to able to improve the partner's knowledge and skills in the accounting recording process based on SAK EMKM, the application of cash inflows and cash outflows along with making supporting documents, as well as increasing information on funding institutions that can be accessed by MSMEs. The method of implementation is by providing training, socialization and mentoring. The subjects of this program are the owners and all employees of Kumala Bali. The instrument of this program uses a questionnaire which is distributed before and after implementation. The evaluation stage is carried out by seeing whether there is an increase in understanding of the accounting recording process based on SAK EMKM, the application of cash inflows and cash outflows along with making supporting documents, as well as information on funding institutions that can be accessed by MSMEs. The results of the activity show that there is an increase in knowledge and skills in the accounting recording process based on SAK EMKM, the application of cash inflows and cash outflows along with making supporting documents, as well as increasing information on funding institutions that can be accessed by MSMEs.